KEEFEKTIFAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAME EDUKASI WORDWALL TERHADAP MINAT DAN HASIL BELAJAR IPAS SISWA KELAS IV SD GUGUS LARASATI KOTA SEMARANG - Anis Fikri Yatil Aula; Akhmad Junaedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the effectiveness of Problem Based Learning (PBL) with the assistance of the Wordwall educational game on the interest and learning outcomes of fourth-grade IPAS students in elementary schools. This research employs a Quasi Experimental Design utilizing a Nonequivalent Control Group Design. The sample consisted of 16 students from class IV at SDN Pakintelan 03 and 20 students from class IV at SDN Pakintelan 02 in Semarang City. Both groups were comparable in terms of initial abilities prior to treatment. After treatment, the experimental group showed statistically significant differences in average interest and learning scores compared to the control group, as evidenced by significance tests yielding a p-value of <0.05. The results of hypothesis testing regarding the effectiveness of interest and learning outcomes also yielded a significance value of <0.05. Therefore, it can be concluded that the application of the problem-based learning model supported by the educational game Wordwall is effective for IPAS learning in elementary schools.